The impact of trade liberalisation on the Indonesian food crop sector : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Economics at Massey University - Da Costa, Helder (Massey University, 1994)
Studies of agricultural trade policies in developed countries generally focus their attention on impacts in their own domestic markets. Less attention has been given to impacts on developing countries nor their need for special and differential treatment in multilateral trade negotiations. This study assesses the impacts of trade liberalisation by modelling the outcome of the Uruguay Round of GATT negotiations. The removal of support in the industrialised nations on the Indonesian food crops sector was examined. Using the Static World Policy Simulation (SWOPSIM) model of world agricultural trade, the impacts on Indonesian consumption, production and net trade were estimated. The results indicate that Indonesian exports of corn would expand, and the country could also become an exporter of rice. Imports of sugar could expand partly as a result of a reduction in Indonesian sugar subsidies. While multilateral trade liberalisation that results in higher world prices may have a negative effect on food importing developing countries, this was found not to be the case for Indonesia (at least for the food crops studied). The increase in producer welfare would more than compensate for the fall in consumer welfare, government subsidy expenditures would fall and the country's trade balance would improve. In addition, continuing unilateral deregulatory and liberalisation measures in other sectors of the Indonesian economy, as well as in agriculture, will provide scope for the development of further new export opportunities.
Keywords: Indonesia; Free trade; Produce trade; Korea; General Agreement on Tariffs and Trade (Organisation); Agriculture -- Economic aspects; Tariff on farm produce